Technoeconomic evaluation of trigeneraton plant: Gas turbine performance, absorption cooling and district heating - Polyzakis, Apostolos (Cranfield University, 2006)
This PhD thesis is a demand led study taking into account changes in ambient conditions and power settings of a tri-generation power plant. Includes an evaluation tool for combined heat, cooling and power generation plant. The thesis is based on an overall technical-economic analysis of the tri-generation system, including: 1. Energy demand analysis and evaluation of actual tri-generation case studies. 2. Modelling of the prime mover (Gas Turbine, GT) 3. Modelling of the absorption cooling system, (LiBr/Water). 4. Economic analysis and evaluation of the entire tri-generation plant. Initially, the main effort is to carry out research concerning the energy demands of different actual cases. The research includes sourcing, collecting, classification and evaluation of the available information. The cases cover a wide range of economic life and the resulting data specifies the energy needs which the purposed tri-generation power plant needs to cover. The second part deals with the prime mover (namely the Gas Turbine, GT) modelling and simulation. The technical part of the assessment includes the Design Point (DP) and Off Design (OD) analysis of the GT. In other words, the performance analysis simulates different thermodynamic cycles (Simple, or with Heat Exchanger), and different configurations (one or two shafts). Also, the computer programming code is capable of simulating the effects of the use of different types of fuel, ambient conditions, part load conditions, degradation, or the extraction of power for district heating or for absorption cooling. The third part includes the simulation of the absorption cooling system alone and/or in co-operation with the prime mover. The simulation is based upon the premise that the original prime mover is replaceable. Finally, an evaluation methodology of tri-generation plants, is introduced taking into account, both technical facts and economic data -based on certain cases from Greek reality- helping the potential users to decide whether it is profitable to use such technology or not. The economic scene will include the basic economic facts such as initial cost, handling and operational cost (fuel prices, maintenance etc), using methodology based on Net Present Value (NPV). This thesis suggests several tri-generation technology modes. The more economic favourable than the conventional technology is the 2-shaft simple cycle mode for the cases of international airport (12MW total power demand) and the isolated island (120MW), while the 1-shaft simple cycle mode is the more economic favourable for the case of hotel (1MW). The main contribution of the thesis is that it provides an intergraded realistic tool, which simulates the future operation (technical and economic) of a trigeneration plant, capable of helping the potential investor decide if it is profitable to proceed with the investment.